Production of three-dimensional fiber needle-punching composites from denim waste for utilization as furniture materials. (25th January 2021) - Meng, Xue; Fan, Wei; Wan Mahari, Wan Adibah; Ge, Shengbo; Xia, Changlei; Wu, Fan; Han, Ling; Wang, Shujuan; Zhang, Minglong; Hu, Zhe; Ma, Nyuk Ling; Van Le, Quyet; et al.
Abstract: The recycling and reuse of denim waste are key challenges towards sustainable disposal of waste textiles. Here we produce high mechanical three-dimensional denim waste fiber needle-punching composites (3DDWNCs) from denim waste through a nonwoven needle-punching process. The impact exerted by fiber volume fraction and needled density on the mechanical performance of 3DDWNCs are studied. The optimum mechanical properties of the 3DDWNCs are obtained at 27.16% of fiber volume fraction and 373 needles/cm 2 of needled density. The addition of denim waste fibers substantially enhanced the mechanical performance of the 3DDWNCs with higher tensile strength (21.83%), tensile modulus (52.38%), flexural strength (49.29%), and flexural modulus (69.38%) compared to that made from pure epoxy resin. The flexural modulus and thickness swelling rate of the 3DDWNCs are superior according to the standard of particle boards, thus showing enormous potential as alternative raw materials to make furniture products such as particle boards, plywood, and desks. Graphical abstract: Image 1 Highlights: A new nonwoven needle-punching approach is developed to utilize waste denim. Waste denim becomes 3D textile composites with desirable mechanical properties. It shows 27% of fiber volume content and 373 needles/cm 2 of needled density. It has higher bending modulus, lower thickness swelling rate than particle board. The composite is non-hazardous with potential application as furniture materials.